2015
DOI: 10.5539/ibr.v8n3p133
|View full text |Cite
|
Sign up to set email alerts
|

The Review of Human Resource Strategies Applying in Hospitality Industry in South California

Abstract: Globalization and interactions through boarders is the major contributor to widespread improvement in many sectors across the economy and has given rise to new innovations incorporated talent with clients. This has led to a significant improvement in the hospitality sector as one of these economic strongholds incorporated with talent management as the backbone given the number of qualified personnel in the sector. The hospitality sector is inclusive of a number of interrelated businesses components such as-air… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Holbrook (1999) simplified the definition of efficiency by characterizing it as the ratio of outputs to inputs. Although efficiency may be achieved via different factors, a number of authors (Sánchez-Fernández and Iniesta-Bonillo, 2009;Shieh et al, 2014;Hsu, 2015) have emphasized the time and monetary components involved in assessing the concept of efficiency. This implies that customers' perceptions of efficiency are evaluated by what they have obtained (goods, services) relative to what they have sacrificed (money, time and effort).…”
mentioning
confidence: 99%
“…Holbrook (1999) simplified the definition of efficiency by characterizing it as the ratio of outputs to inputs. Although efficiency may be achieved via different factors, a number of authors (Sánchez-Fernández and Iniesta-Bonillo, 2009;Shieh et al, 2014;Hsu, 2015) have emphasized the time and monetary components involved in assessing the concept of efficiency. This implies that customers' perceptions of efficiency are evaluated by what they have obtained (goods, services) relative to what they have sacrificed (money, time and effort).…”
mentioning
confidence: 99%
“…The TH industry is service-oriented (Hsu, 2015) and labor-intensive (Grolber & Diedricks, 2009), and it depends on identifying and employing superior talents (Barron, 2008) through TM (Meyers & Woerkom, 2014). As managers and employers engaged in this industry have acknowledged, talent can make it possible for a business to distinguish itself from competitors and ultimately contribute to the success of a business (D'Annunzio-Green, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is suggested that the practices of talent management need to reflect the uniqueness and complexity of the organizations need and take its dimension more seriously because it will improve employer branding and will directly have an impact upon the quality of applications received by the organizations. Without talent, hospitality and tourism have no dynamism, globally, talented people are at the heart of successful hospitality and tourism organizations and businesses (Mathew, 2015;Hsu, 2015;Nzonzo and Chipfuva, 2013). The objectives of this study involve: (1) determine the effect of talent management dimensions on employee performance criteria, (2) examine the relationship between talent management strategies and employee performance, (3) understand the hotel's view on implementation of talent management practices.…”
Section: Introductionmentioning
confidence: 99%